Linguistically Packaging Opinion: A Quantitative Token-Based Analysis of Adjective Structures in English - Brosa-Rodríguez, Antoni (Research in Language, 2025)
This study examines the distribution and characteristics of three linguistic structures across three different semantic types of adjectives in English: opinion-based (evaluative), mixed (dimensional), and non-opinion (objective) adjectives. While previous research has explored the perception of subjective adjectives in varied linguistic environments through experimental methods, our research provides quantitative corpus-based evidence from Universal Dependencies English corpora. The analysis focuses on three syntactic structures: modification of a noun (Adj+Noun), predicative construction with nexus (Nexus+Cop+Adj), and predicative construction with noun subject (Noun+Cop+Adj). Results reveal significant patterns: opinion adjectives display greater structural flexibility, appearing with meaningful frequency in both attributive and predicative positions, while dimensional adjectives strongly favor attributive position. The study also identifies consistent positional patterns across all adjective types, with attributive structures typically appearing later in sentences than predicative constructions. Furthermore, register variations were observed, with web language showing distinctive distributional patterns for opinion adjectives compared to more varied texts.